Inovasi Pembelajaran Berbasis Proyek: Budidaya Hidroponik Oleh Siswa SMK Negeri 1 Siau Timur - Howan, Dian; Rengkuan, Mariana; Rumondor, Desire Atna Sridanty; Lambe, Livianni; Zachawerus, Karuniawati (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
State Vocational High School (SMK) 1 Siau Timur is one of the vocational schools in Sitaro Regency that has great agricultural potential, but has never conducted a hydroponic farming learning project. This Community Service (PKM) activity aims to increase student empowerment through hydroponic cultivation training as an innovative solution to support local food security, as well as strengthening entrepreneurial competencies. This program is implemented using the Project-Based Learning (PjBL) method with stages of theoretical training, seeding practice, hydroponic installation assembly, and plant care. A total of 40 students majoring in Agribusiness and Agricultural Product Processing (APHP) became active participants in this activity. The results of the training survey showed a significant increase in the aspects of knowledge, technical, skills, and student confidence. 82.5% of students considered the activity very useful and 75% stated that their practical abilities increased. This activity proves that the hydroponic system is effective as an innovative learning tool based on local potential that can be integrated into the school curriculum to encourage food independence and develop students' entrepreneurial spirit.